2014
DOI: 10.1111/bph.12717
|View full text |Cite
|
Sign up to set email alerts
|

Dipyrone metabolite 4‐MAA induces hypothermia and inhibits PGE2‐dependent and ‐independent fever while 4‐AA only blocks PGE2‐dependent fever

Abstract: BACKGROUND AND PURPOSEThe antipyretic and hypothermic prodrug dipyrone prevents PGE2-dependent and -independent fever induced by LPS from Escherichia coli and Tityus serrulatus venom (Tsv) respectively. We aimed to identify the dipyrone metabolites responsible for the antipyretic and hypothermic effects. EXPERIMENTAL APPROACHMale Wistar rats were treated i.p. with indomethacin (2 mg·kg ) or saline. Rectal temperatures were measured by tele-thermometry and dipyrone metabolite concentrations determined in the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
1
19
0
4
Order By: Relevance
“…This response is elicited by exogenous pyrogens and promoted by the endogenous ones such as IL-1β, IL-6, TNF-α, endothelin-1 (ET-1), corticotrophin release factor (CRF), bradykinin, preformed pyrogenic factor (PFPF), and prostaglandin E2 (PGE2) [24]. PGE2-dependent fever results mainly by the action of the activated cyclooxygenase enzymes in the preoptic zone of the hypothalamus [25]. Brewer's yeast injection in mice raised their rectal body temperature when measured 18 h following the injection (Table 3).…”
Section: Effect Of Extracts On Brewer's Yeast Induced Pyrexia In Micementioning
confidence: 99%
“…This response is elicited by exogenous pyrogens and promoted by the endogenous ones such as IL-1β, IL-6, TNF-α, endothelin-1 (ET-1), corticotrophin release factor (CRF), bradykinin, preformed pyrogenic factor (PFPF), and prostaglandin E2 (PGE2) [24]. PGE2-dependent fever results mainly by the action of the activated cyclooxygenase enzymes in the preoptic zone of the hypothalamus [25]. Brewer's yeast injection in mice raised their rectal body temperature when measured 18 h following the injection (Table 3).…”
Section: Effect Of Extracts On Brewer's Yeast Induced Pyrexia In Micementioning
confidence: 99%
“…The presence of the dipyrone metabolites 4-MAA and 4-AA in cerebrospinal fluid and the hypothalamus was associated with inhibition of PGE 2 synthesis and a reduction in lipopolysaccharide-induced fever; 59,60 however, 4-MAA has also been shown to be antipyretic in PGE 2 -independent fever induced by Tityus serrulatus venom. 59 This suggests that 4-MAA is responsible for the PGE 2 -independent antipyretic activity of dipyrone 59 because it was not mechanistically linked to the inhibition of hypothalamic PGE 2 synthesis. 60 Both dipyrone and cannabinoid agonist treatment evoked hypothermia and a CB 1 receptor antagonist blocked the analgesic, hypolocomotion and catalepsy responses to dipyrone.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that a CB1 receptor inverse agonist and an anti-sense oligonucleotide against CB1 receptors reversed the anti-hyperalgesic effect of 3, but not that of dipyrone or 2 (Dos Santos et al, 2014). Finally, it was reported that 2 induced hypothermia and inhibited PGE 2 -dependent and -independent fever, while 3 only inhibited PGE 2 -dependent fever (Malvar et al, 2014).…”
Section: Introductionmentioning
confidence: 94%